Chunk Size Optimisation for Improved Sensory Quality of Restructured Beef - Basha, M H S Abrar; Sathu, T; Vasudevan, V N; Irshad, A; Gleeja, V L; Tahseen, Aaliya (Journal of Meat Science, 2023)
The research aimed at standardisation of chunk size for cold-set restructured beef prepared using microbial transglutaminase (MTGase) as binding agent. Type II quality beef cuts, includes round and chuck were mixed in 1:1 ratio and compared at three different dimensions viz., T1 [7.5 cm (Breadth) × 10 cm (Length) × 5 cm (Thickness)], T2 [10 cm (Breadth) × 10 cm (Length) × 5 cm (Thickness)] and T3 [10 cm (Breadth) × 12.5 cm (Length) × 5 cm (Thickness)]. Microbial transglutaminase and curing agents were used as ingredients. Cold-set beef blocks were created by a series of stages including vacuum tumbling, vacuum packaging, equilibration and freezing. The resulting cold-set beef blocks were then sliced into 5 mm thick beef steaks, seasoned with a spice and cooked. The steaks were subjected to sensory evaluation both as raw and cooked. Sensory evaluations indicated that smaller chunk sizes resulted in a more favourable sensory experience, particularly in terms of appearance, flavour, tenderness, saltiness, juiciness, cohesiveness and overall acceptability. According to the findings of this study, the chunk size of 7.5 cm (Breadth) × 10 cm (Length) × 5 cm (Thickness) was chosen as the standardized size for cold-setted restructured beef block.
Keywords: Restructured beef block; microbial transglutaminase; chunk size; sensory evaluation; standardisation